Profile of Pediatric Cataract Seen at Lagos University Teaching Hospital, Lagos, Southwest Nigeria - Olatunbosun, Musa Kareem; Temitayo, Aribaba Olufisayo; Ikuomenisan Segan Joseph, Rotimi-Samuel Adekunle; Olayinka, Oluwoyeye Abimbola; Olukorede, Onakoya Adeola (Pakistan Journal of Ophthalmology, 2018)
Purpose: To describe the characteristics of pediatric cataracts seen at Lagos University Teaching Hospital, Lagos, Nigeria. Study Design: Retrospective descriptive study. Place and Duration of Study: Pediatric Ophthalmology Clinic, Department of Ophthalmology (Guinness Eye Centre), Lagos University Teaching Hospital, Lagos, Nigeria between January, 2012 and December, 2015. Materials and Methods: A retrospective review of the case files of all children below the age of 16 years, who had diagnosis of cataract was done. Information retrieved from the case files included demographics, laterality, duration before presentation, family history of childhood cataract, pregnancy and delivery history, preceding history of trauma, type of cataract, ocular and systemic co-morbidities as well as serological test result for intrauterine (in congenital cataract). Results: Three hundred and thirteen eyes of 210 children with cataract were analyzed. There were 153 (72.9%) non-traumatic cataract and 57 (27.1%) traumatic cataract. The 153 non-traumatic cataract were made up of 78 (37.2%) congenital cataract, 62 (29.5%) developmental cataract as well as 13 (6.2%) complicated cataract. There were 132 (62.9%) males and 107 (50.9%) children had unilateral cataract. Only 79 (37.6%) children presented within three months of the onset of symptoms. One and two children were positive for cytomegalovirus and rubella IgM antibodies respectively. Forty-five (78.9%) out of the 57 children with traumatic cataract sustained ocular injury while playing or being flogged either at home or school. Conclusion: Trauma and rubella were the main preventable causes of pediatric cataract identified in this study. Late presentation was the case in the majority of the patients. Keywords: Pediatric Cataract, Lagos, Nigeria, Rubella.